Peripartum Cardiomyopathy in a Patient with Undiagnosed Persistent Patent Ductus Arteriosus (PDA): A Rare Clinical Association (University Heart Journal, 2026)
Peripartum cardiomyopathy (PPCM) is a rare form of heart failure occurring in late pregnancy or early puerperium, typically in women without pre-existing heart disease. This report details the rare co-existence of PPCM and an uncorrected Patent Ductus Arteriosus (PDA). A 19-year-old woman, diagnosed with PPCM (EF-43%) during her late pregnancy, presented with heart failure symptoms (NYHA Class II dyspnea). Physical examination revealed a classic Grade 4/6 continuous machinery murmur. Echocardiography confirmed a moderate PDA (≈4mm) with a significant left-to-right shunt (Qp/Qs-2.1), after conservative treatment her heart failure symptoms were improved with a preserved Left Ventricular Ejection Fraction (EF-62%). The symptoms were primarily driven by PDA-induced volume overload. The patient underwent successful transcatheter PDA closure. This case emphasizes the critical need for heightened clinical vigilance to evaluate cardiopulmonary symptoms in pregnant women, as their presentation can be confused with normal pregnancy changes, delaying diagnosis causes serious underlying cardiac issues.University Heart Journal 2026; 22(1): 44-48